Penerapan Business Judgement Rules Dalam Badan Usaha Milik Negara Studi Kasus PT Asuransi Jiwasraya - Franky Ariyadi (Universitas Muhammadiyah Tangerang, 2020)
In the case of PT Asuransi Jiwasraya, the company’s management decision caused the company to suffer a loss. To prove whether the Business Judgement Rulr can be used to protect the decisions that have been made, surely it must proven first: how the decision process is made, both from the legal aspects of the company and the criteria for the Business Judgement Rule.